Evaluating The Effectiveness Of An Efl Module In Enhancing Critical Thinking, Writing And Collaborative Skills Of Omani Efl Foundation Students - Abdelmohsen Ibrahim, Moustafa Mohamed (2021)
Writing is deemed one of the salient skills that students need to master since it demands a more substantial in-depth knowledge of the grammar system and writing conventions than other receptive skills. For this reason, Omani students are required to have a mastery of writing to satisfy the requirements of higher education writing level where writing is deemed the most suitable assessment method of students‟ academic progress. Nevertheless, the General Foundation Program students are unable to generate and organize ideas, write a sound thesis statement, use a wide range of vocabulary, or maintain paragraphs unity, cohesion, and coherence. Another problem is related to students‟ dearth of critical thinking ability and collaborative skills in writing. To this end, the current study developed a writing module to enhance the writing, critical thinking, and collaborative skills of the Omani Foundation Program students using ADDIE model. The study used a pre-test and post-test quasi-experimental design. The study employed three instruments: the pre-test and post-test, students‟ reflective journals, and semi-structured interviews. The participants were 70 Omani students and 2 EFL teachers. The students were divided into experimental and control groups. The experimental group incorporated 35 students and the control group involved 35 students as well